Clinical validation of urine 3-methoxytyramine as a biomarker of neuroblastoma and comparison with other catecholamine-related biomarkers. (March 2017) - Lam, Leo; Woollard, Gerald A; Teague, Lochie; Davidson, James S
Background: Urinary dopamine, homovanillic acid and 4-hydroxy-3-methoxymandelic acid are established tests for diagnosis and monitoring of neuroblastic disease. We compared the diagnostic performance of total urinary 3-methoxytyramine, the O-methylated product of dopamine, to these three established tumour markers. Methods: Urinary 3-methoxytyramine, dopamine, homovanillic acid and 4-hydroxy-3-methoxymandelic acid were measured by high-performance liquid chromatography with electrochemical detection on consecutive urine samples from histologically proven neuroblastic patients and controls. Patients with neuroblastic disease were further classified as untreated, advancing, residual or absent disease based on clinical and radiological criteria. Receiver operating characteristic curve analysis was used to compare the diagnostic performance of the four tumour markers. Results: Urinary 3-methoxytyramine was well correlated with established tumour markers and its concentration correlated with disease activity. It was the most commonly elevated tumour marker in neuroblastic disease and showed similar sensitivity to dopamine and homovanillic acid. The diagnostic utility of urinary 3-methoxytyramine as measured by area under the receiver operating characteristic curve was similar to dopamine and homovanillic acid. Conclusion: Our results support the use of urinary 3-methoxytyramine as a tumour marker in the diagnosis and the monitoring of neuroblastoma disease.